Research on Linkage Accuracy of "Baby Hanging Basket" Five-axis Precision Machine Tool - Wu, Yuanyuan; An, Huiling; Li, Bo; Zhang, Hua; Hu, Lai (Manufacturing Technology Journal, 2024)
The "baby hanging basket" five-axis precision machine tool (BHBFPMT) studied in this study is mainly used to process open impeller and closed impeller in aerospace field. However, the linkage accuracy (LA) measurement of five-axis machine tool is one of the important detection means to ensure the tolerance requirements of precision parts. The mathematical model of linkage accuracy (LA) of "baby hanging basket" five-axis precision machine tool (BHBFPMT) was established. The accuracy of X, Y, Z, B and C axes was measured, respectively. Combined with the measurement results, a pulse compensation method was proposed to compensate the accuracy. The linkage accuracy of the machine tool was analyzed by the machining and precision measurement method of "round-rhombic-square" trial cutting parts. The results show that: (1) In single-axis measurement, the positioning accuracy of X, Y, Z, B and C axes are 0.00096 mm, 0.00261 mm, 0.00173 mm, 0.0113 mm and 3.62 '', respectively. (2) When the pulse changes of B axis and C axis are 1048630 and 1048596, respectively, the positioning accuracy meets the accuracy requirements of "baby hanging basket" five-axis precision machine tool. (3) By measuring and analyzing the accuracy of "round-rhomb-square" test pieces, the linkage accuracy of "baby hanging basket" five-axis precision machine tool is less than 20 μm, which meets the factory standards and precision requirements of machine tool.
Keywords: "Baby hanging basket" five-axis precision machine tool (BHBFPMT); Linkage accuracy (LA); Precision; Measurement; Pulse compensation